THE ROLE OF GUIDANCE AND COUNSELING IN ROMANTIC CONFLICT - Serios, Jonavie N (Universitas Muria Kudus, 2023)
Conflict in romantic relationships is a common experience for adolescents and young adults. Not only does conflict disrupt relationship quality, it also has a negative impact on mental health, triggering anxiety, decreased self-confidence, and even depression. This study examines the important role of counseling in helping individuals experiencing conflict in romantic relationships. This study analyzes the experiences of individuals who have experienced conflict and have attended counseling. It turns out that counseling, especially with the CBT (Cognitive Behavioral Therapy) method, can help them change negative thinking into more positive ones. They became better able to control their emotions, communicate more effectively, and build healthier relationships. Counseling also helps them see conflict as an opportunity to learn and grow, not just a problem to be avoided. They become more emotionally independent, more confident, and able to set clear boundaries in relationships. This research shows that although romantic conflict is painful, counseling can be a solution to turn hurt into strength. With the help of the right counselor, individuals experiencing conflict can recover mentally and build healthier relationships in the future.